Evaluation of a new thromboplastin reagent STA‐NeoPTimal on a STA R Max analyzer for the measurement of prothrombin time, international normalized ratio and extrinsic factor levels. (19th May 2020) - Mullier, François; Paridaens, Marie‐Sophie; Evrard, Jonathan; Baudar, Justine; Guldenpfennig, Maité; Devroye, Celia; Miller, Laurence; Chatelain, Bernard; Lessire, Sarah; Jacqmin, Hugues
Abstract: Introduction: We aimed at evaluating the performance of a new prothrombin time (PT) reagent (STA‐NeoPTimal) with two other PT reagents (STA‐Neoplastine R and STA‐Neoplastine CI Plus) and the reference PT reagent used in our laboratory (ReadiPlasTin). Methods: Evaluation consisted in intra‐ and interassay precision assessment, determination of sensitivity to unfractionated heparin (UFH) or enoxaparin in spiked samples and to direct oral anticoagulants (DOACs) in patients (n = 43). Method comparison of the 4 PT reagents, factor II, V, VII and X assays was tested on normal (n = 20) and abnormal samples: VKA (n = 47), preoperative (n = 23), liver failure (n = 12) and burned patients (n = 37). Results: Analytical performance met manufacturers' criteria for all reagents. All PT reagents gave correlation coefficients >0.8 and even >0.9 in many situations. In some VKA samples, differences ≥ 0.5 INR units were found in samples within and above therapeutic ranges. For burned patients, PT correlations were good but with some minimal bias (<5.0%) while factor assays gave very consistent results ( R > .8 and mainly >0.9). As expected, poor responsiveness of the PT to DOAC concentrations was observed with all four assays. Conclusion: The STA‐NeoPTimal showed comparable performance to ReadiPlasTin, making it suitable for VKA control, detection of factors II, V, VII, X deficiency and assessment of liver disease coagulopathy. However, for patients receiving VKA, some significant differences were observed. We confirmed the inability of the PT assay to detect residual DOAC concentrations. Finally, burned patients results showed that recombinant thromboplastins were less sensitive to factor deficiencies in comparison to extraction thromboplastins.